If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + X = -36 Solving 5 + X = -36 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + X = -36 + -5 Combine like terms: 5 + -5 = 0 0 + X = -36 + -5 X = -36 + -5 Combine like terms: -36 + -5 = -41 X = -41 Simplifying X = -41
| 2y+7=35 | | h=16t^2+52t+16 | | 4.95+11.95=64.70 | | 40+2m=-8(m+5) | | x+74+36=77 | | 5(x-3)-4(x-3)=3(x-1) | | 2x^4-10x^2+5=0 | | 10t^2-17t+6=0 | | -4w+8=-8(w+3) | | 0.23*50=1*x | | -4z=126 | | 3x-10(x+2)=1.22-7x | | 8x-1=-9+7x | | 3x+2x+8=7x-2 | | 5y=15y-90 | | x+38+90+x+68=180 | | -6(-1-6b)=-138 | | 4(x+6)=y-2 | | -8v+6(10+6v)=-10(v-7)-7(v+2) | | -3(x-4)+5=14 | | 3s-6=10+3s | | 16(x+1)-1=14(x+1) | | 4x=3(y+3) | | x+59+50=80 | | 2x^2-8=15x | | -8-x=13 | | 15=-(12-z) | | b-8+6b=26 | | 12x-7=2x-6 | | -24=-3+3v | | (x^2-4x+4)(-x^2+8x-17)=0 | | x=n+8 |